Literature Review: Pengaruh Daun Katuk (Sauropus Androgynus) Terhadap Peningkatan Produksi ASI Pada Ibu Menyusui - izhar ibrahim; Ayu Pratiwi (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2021)
ABSTRATC Background: According to Tangerang District Health Office data for 2018, excruciating breastfeeding coverage increased from 42.36% in 2012, 44.92% in 2013, and 47% in 2017. Many mothers worry about giving enough breast milk because the signs of breast milk adequacy cannot be measured from the amount of breast milk given directly through breastfeeding. Purpose: This study aims to determine the efficacy of katuk leaves against increased breast milk production in nursing mothers. Method: This study is a literature review on the efficacy of katuk leaves against increased breast milk production. Sources for conducting this literature review include systematic search studies of computerized databases with PICO format (population, intervention, comparasion, and outcome) in the form of research totaling 9 journals (Integrated Health Journal, Naska Publikasi Poltekkes Kemenkes Semarang, Jurmal Majority, Jurnal Saintika, Published Paper of The Health Polytechnic Of the Ministry of Health, Indonesian Journal for Health Sciences, Indonesian Trust Health Journal, Journal of Healthcare and Journal of Nursing Care Management). Results: The study found participants consumed katuk leaves by consuming katuk leaf extract 2 capsules 2x1 day, simplisia method 2x1 day 150ml, decoction of katuk leaves 3x150ml. Conclusion: Based on a search article found in 9 journals obtained that all articles found stated that there is an effective influence between the consumption of katuk leaves on the increase in breast milk production either by consuming katuk leaves by being processed into clear vegetables, katuk leaf extract, katuk leaf stew, or processed into biscuits or snacks for breastfeeding mothers. Advice: Hopefully the results of exposure in the article found can motivate breastfeeding mothers to try to consume katuk leaves as an additional intake to increase breast milk production. Keywords: Sauropus Androgynus, breast milk